눈물소관 폐쇄에서 눈물소관 원형절제술을 동반한 코경유 눈물주머니코안연결술의 임상결과 - 한수연(Su Yeon Han); 오재현(Jae Hyun Oh); 김상덕(Sang Duck Kim) (Daihan angwa haghoi jabji, 2024)
목적: 눈물소관 폐쇄 환자에서 눈물소관 원형절제술을 동반한 코경유 눈물주머니코안연결술의 수술 효과를 알아보고자 하였다. 대상과 방법: 2010년 5월부터 2022년 7월까지 눈물소관 폐쇄로 진단받고 눈물소관 원형절제술과 함께 코경유 눈물주머니코안연결술을 시행 받은 환자 32명 37안의 의무기록을 후향적으로 분석하여 수술성공률 및 합병증을 조사하였다. 결과: 전체 환자군에서 눈물 흘림이 완전히 소실된 완전한 성공(complete success)은 81.1%, 눈물흘림 증상이 남아있으나 호전된 부분적 성공(partial success)은 13.5%였으며, 눈물흘림이 지속 혹은 악화된 실패(failure)는 5.4%였다. 추적관찰 중 발생한 합병증에는 비강내 육아종 1예, 골공 염증 1예가 있었다. 결론: 눈물소관 폐쇄에서 눈물소관 원형절제술을 동반한 코경유 눈물주머니코안연결술은 수술성공률이 높고 합병증이 적은 효과적인 수술 방법으로 생각되며, 고식적인 치료방법인 결막눈물주머니코안연결술 전 시도해 볼 수 있는 방법이다. Purpose: To investigate the surgical outcomes of endonasal dacryocystorhinostomy with canalicular trephination in patients with canalicular obstruction. Methods: We retrospectively analyzed the medical records of 37 eyes from 32 patients who were diagnosed with canalicular obstruction between May 2010 and July 2022 and underwent endonasal dacryocystorhinostomy with canalicular trephination to evaluate the success rate and complications. Results: In the total patient group, 81.1% achieved complete success in which epiphora completely disappeared, 13.5% had partial success in which epiphora remained but improved, and 5.4% experienced failure in which tearing persisted or worsened. Complications included one case of dacryocystorhinostomy bony opening granuloma and one case of dacryocystorhinostomy bony opening inflammation. Conclusions: Endonasal dacryocystorhinosomy with canalicular trephination is an effective method for treating canalicular obstruction, offering a high success rate and few complications. It can be considered before resorting to conjunctivodacryocystorhinostomy, which is a more conventional treatment. KCI Citation Count: 0